Estimating the impacts of Bolivia's protected areas on poverty - Gustavo Javier Canavire-Bacarreza; Merlin M. Hanauer (Institute for the Study of Labor (IZA), 2012)
Protected areas represent a powerful policy tool for the preservation of ecosystems and their services. The rapid proliferation of protected areas in Bolivia over the past several decades has prompted interest in understanding their impacts on surrounding populations. Recent studies from other developing countries show that protected areas have had positive impacts on poverty. Using rich biophysical and socioeconomic data from Bolivia we find that municipalities with at least 10% of their area occupied by a protected area established between 1992 and 2000 exhibited differentially greater levels of poverty reduction between 1992 and 2001 compared to similar municipalities unaffected by protected areas. We find that our results are robust to a number of econometric specifications, spillover analyses and a placebo study. Although our overarching results that Bolivia's protected areas were associated with poverty reduction are similar to previous studies, our underlying results differ subtly, but significantly. Previous studies found that controlling for key observable covariates led to fundamentally antithetical results compared to naive (uncontrolled) estimates. Conversely, our results indicate that naive estimates lead to an over estimation of the poverty reducing impacts of protected areas. Our results expose the heterogeneity of protected area impacts across countries and, therefore, underscore the importance of country-level impact evaluations in order to build the global knowledge base regarding the socioeconomic impacts of protected areas.
urn:nbn:de:101:1-201205026070
Keywords: C14; I38; Q56; 330; ecosystems; poverty; protected areas; impacts; program evaluation; econometrics; Bolivia; Naturschutz; Armut; Armutspolitik; Bolivien